2020
DOI: 10.1111/cxo.13047
|View full text |Cite
|
Sign up to set email alerts
|

Macular and peripapillary vessel density in myopic eyes of young Chinese adults

Abstract: The aim of this study was to compare the macular and peripapillary vessel densities in eyes of young Chinese adults with different degrees of myopia and to evaluate the association of macular and peripapillary vessel densities with axial length and retinal nerve fibre layer thickness. Methods: A total of 128 eyes (mild myopia, 42; moderate myopia, 45; severe myopia, 41) underwent optical coherence tomography angiography imaging. Parameters assessed were vessel densities in the superficial capillary plexus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…To be clear, several ocular factors have strong association with peripapillary vessel density in healthy eyes. Consistent with other studies (22)(23)(24), the longer the axial length, the lower the retinal VD in the peripapillary area. Reduced vessel density was observed with more myopic eyes.…”
Section: Discussionsupporting
confidence: 92%
“…To be clear, several ocular factors have strong association with peripapillary vessel density in healthy eyes. Consistent with other studies (22)(23)(24), the longer the axial length, the lower the retinal VD in the peripapillary area. Reduced vessel density was observed with more myopic eyes.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the presented data, whole vessel density at both the superficial and deep macular layers was significantly lower in HM eyes which strongly supports the findings from Yang et al [11], Fan et al [26], and Yang et al [29] studies. However, Yang et al [27] reported contrary findings showing no significant differences across various levels of myopic severity.…”
Section: Discussionsupporting
confidence: 91%
“…Extensive studies have revealed associations between excessive eyeball elongation and various vascular abnormalities in myopic eyes (refer to Zhao et al for a recent review 3 ). At the retinal level, myopic eyes showed reduced capillary perfusion at foveal 4 , 5 and peripapillary regions 6 , 7 , enlarged foveal avascular zone 8 , 9 , narrower retinal vessels 10 , and higher percentage of peripheral avascularity 11 .…”
Section: Introductionmentioning
confidence: 98%